Makers of the microchip a documentary history of Fairchild Semiconductor - Lécuyer, Christophe (MIT Press, 2010)
"In the first three and a half years of its existence, Fairchild Semiconductor developed, produced, and marketed the device that would become the fundamental building block of the digital world: the microchip. Founded in 1957 by eight former employees of the Shockley Semiconductor Laboratory, Fairchild created the model for a successful Silicon Valley start-up: intense activity with a common goal, close collaboration, and a quick path to the market (Fairchild's first device hit the market just ten months after the company's founding). Fairchild Semiconductor was one of the first companies financed by venture capital, and its success inspired the establishment of venture capital firms in the San Francisco Bay area. These firms would finance the explosive growth of Silicon Valley over the next several decades. This history of the early years of Fairchild Semiconductor examines the technological, business, and social dynamics behind its innovative products. The centerpiece of the book is a collection of documents, reproduced in facsimile, including the company's first prospectus; ideas, sketches, and plans for the company's products; and a notebook kept by co-founder Jay Last that records problems, schedules, and tasks discussed at weekly meetings. A historical overview, interpretive essays, and an introduction to semiconductor technology in the period accompany these primary documents"--P. [2] of dust cover.
Includes facsimiles of historical documents.
Keywords: Fairchild (Firm) -- History.; Fairchild (Firm) -- Archives.; Semiconductors -- Design and construction -- History.; Integrated circuits -- Design and construction -- History.; Fairchild (Firm); elektronické knihy; electronic books